Disclosure of Foreign Currency Transaction and Translation by Indian Companies - Sharma, Jyoti (Indian Journal of Finance, 2011)
The main objective of the study is to analyze the disclosure of the information on Foreign Currency Transaction and Translation in the Annual Reports of the selected companies in India for financial year 2007. The scope of the study consists of the analysis of disclosure practices of 205 Indian companies in relation to Effects of Changes in Foreign Exchange Rates (Accounting Standard-11 (Revised 2003)). The analysis is further examined into three sections i.e. Item-wise Disclosure Analysis, Company-wise Disclosure Analysis and Industry-wise Disclosure Analysis. Content Analysis has been used to convert qualitative data into quantitative prospective. From the overall results of item-wise and company-wise disclosure, it has been observed that software/ITes&Peripherals industry can be accreted as best. All the companies in Software industry are having a disclosure score of 100% in case of compulsory disclosure practices. The main reason behind such good disclosure practices is that these companies have their working internationally, so they are required to follow international rules and regulations. The other reason may be that due to the changed behaviour of the investors, the company is obligatory to give true and fair knowledge in order to satisfy the shareholders.